Some palmist traditions about the period 1821-1824 - Arroyo Laguna, Eduardo (2023)
In this article, we discuss some ideas about the evolution of these two centuries of our independence and how, since there have been no changes in substance, the insurgent and libertarian figure of Palma grows and becomes bicentennial. We put the weight on some traditions that reflect the incidences of episodes previous to our independence between 1821 and 1824. Keywords: Independence, Centennial, Bicentennial, Republic, Official Peru, and Deep Peru.